Itinerarios de una apropiación crítica: Raikō y La araña de tierra - García Rodríguez, Amaury A. (El Colegio de México, 2010)
This article explores the literary, theatrical and iconographic backgrounds associated with the story of Minamoto Yorimitsu and the earth spider. Proceeding from the standpoint of editorial censorship during the first half of the 19th century in Japan, it focuses on how the population of the city of Edo, as well as illustrators and publishers, used this tale with a critical aim. From a detailed study of an ukiyo-e woodblock prints on the subject, made by Utagawa Kuniyoshi in 1843, the article examines both the alternative versions based on this image—which appeared openly, in violation of government regulations—as well as some of the copies of Kuniyoshi’s prints, which are preserved of in major collections worldwide.